Pengaruh Peran Ayah Terhadap Pembentukan Karakter Remaja - Yoan Olivia; Joko Prihanto (Shema: Jurnal Teologi Injili dan Pendidikan Kristen, 2022)
Fathers play an important role in the life of adolescents, in particular to youth character-building. The study is done to find out how much a father’s role is affected in the formation of a teenager’s character. So the study was carried out in Betania Fresh Anointing Church Bandung with a total of 65 samples. The instrument was a closed questionnaire using a google form. Data processing uses a quantitative method with the help of SPSS software 25. Data validity is gained through validity and reliability. Studies have shown that there is a strong and significant connection between fatherhood and the forming of teenage character. The role of the father has a 69,5% effect on the development of the teen character while the rest is an influence of other factors not studied in the study.